Halitosis - Iba, Bemhemba; FALEGBE, Rapheal Kehinde; ASA, Yomi Isaac; NWAOHABUENYI, Thelma Ebere; IBEOBI, Ada Cynthia (Orapuh Journal, 2021)
Halitosis is an offensive odour emanating from the mouth whose effects are so devastating on the social and psychological state of individuals. Over 50% of the world population is claimed to have halitosis and it is the third commonest complaint patients present to the dental clinic. The objective of this review was to present a succinct discussion on the epidemiology, aetiology, classification, social and psychologic effects, diagnosis, and management of halitosis based on conventional and recently introduced information. An extensive literature review was conducted on several published peer-review journal articles but only articles from 2017-2021 and those written in the English language which fulfilled the study’s inclusion criteria were considered. The review also considered all relevant subject headings such as halitosis, bad breath, oral malodour, and volatile sulfur compounds in PubMed/Medline, Google Scholar, JSTOR, Medscape, and Microsoft academia databases. Several articles were related to the subject area but only 52 full-text articles were used for this review. According to the reviewed articles, the studies pointed to the fact that a multidisciplinary approach is extremely crucial in managing halitosis to assist in identifying the right diagnosis and administering the correct treatment aimed at eliminating the aetiological agents and maintaining proper hygiene. Daily oral hygiene practice with the mechanical removal of dental biofilm using toothbrush and dentifrice, flossing and utilization of antimicrobial agents will significantly reduce the number of microorganisms causing bad breath.